Hybrid Simulations Using Standardized Patients and High Fidelity Mannequins for Anaphylaxis and Asthma Treatments in an Office Setting - Joshua Kennedy; Travis Hill; Grace Gephardt; Mary Cantrell; Tonya Thompson (Association of American Medical Colleges, 2012)
Abstract Introduction In-office medical emergencies can be a source of trepidation for both medical and administrative personnel. Lack of preparation, equipment, training, and communication amongst staff are cited as the most frequent reasons for suboptimal patient care in an office emergency in a general pediatric or family practice clinic. This resource utilizes hybrid simulations using standardized patients and high-fidelity mannequins for anaphylaxis and asthma treatments in an office setting to teach medical students, nurses, residents, and physicians (learners) the importance of prompt treatment of allergic emergencies. Methods Within this resource, we provide three case presentations of patients requiring emergent treatment for allergic emergencies. These cases are considered hybrid scenarios because they require the use of both standardized patients with high-fidelity mannequins. Each simulation has a separate script required to introduce the case. We have also provided a flow diagram for the scenarios that will allow staff members who are responsible for real-time changes in the simulations to make adjustments in the outcomes of these simulations dependent upon learner input. Results We have utilized these simulations in a research study performed at the University of Arkansas Children's Hospital. Participant scores demonstrated improved team management skills with simulation training in office emergencies. Because the true outcome of interest in office emergencies is the outcome of resuscitations, we cannot determine whether utilizing these simulations improved emergency care to actual patients. Discussion Upon seeing the mannequin, some of the learners did not take the scenario seriously, perhaps taking longer than they would to perform an actual emergency resuscitation. We attempted to improve this outcome by stressing the importance of participant buy-in. In postworkshop feedback from learners, subjects felt as if they were responding to a true emergency if the scenario was thrust upon them during other instruction due to its unexpected nature.